2009
DOI: 10.3126/gjn.v7i0.17437
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Patterns of Majhi and Kumal Communities in the Arun Valley, Eastern Nepal

Abstract: The present paper is an attempt to portray the livelihood patterns of two marginalized communities such as Majhi and Kumal of Kumaltar village in the Arun valley, eastern Nepal. Data were collected from all 28 households of both communities. The findings show that agriculture and livestock now are the main occupations for their living. Prior to these, ferrying, fishing and pottering were their traditional occupations when they moved to Kumaltar in several years ago. As the production from agriculture and lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Majhis are expected to push the vessel boat across the watercourse. As a result, they are also involved in angling and cultivating along the waterway (Rai & Majhi, 2014).…”
Section: Traditional Occupation and Livelihoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Majhis are expected to push the vessel boat across the watercourse. As a result, they are also involved in angling and cultivating along the waterway (Rai & Majhi, 2014).…”
Section: Traditional Occupation and Livelihoodmentioning
confidence: 99%
“…Majhi has a distinct culture and customary ways of life (Rai & Majhi, 2014). The Majhi community lives on the banks of the Kali Gandaki River.…”
Section: Transformation In Occupation and The Socio-cultural Life Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Now-a-days, petty business has gradually become popular in the rural areas in Nepal. A study by Rai (2009) in Arun Valley of eastern Nepal and study by Rajbansi (2010) in the peripheral areas of Kathmandu valley have suggested that petty business in the rural areas of Nepal has also become an important base of livelihood in the recent days. Local products such as liquor (local beer and alcohol),grain, vegetables, fruits, livestock (goat, pig, chicken etc.…”
Section: Business: An Unconventional Rural Livelihoodmentioning
confidence: 99%
“…Their livelihood strategies to adapt to the changing environment condition differ over spaces and by social groups; cultural values of people in the same space can create differences in the pattern of adaptation from one ethnic group to another (Subedi and Pandey, 2002). Various studies done in the rural hilly and mountain areas have observed that livelihood strategies of people are shifting from agriculture to nonagriculture based livelihoods such as wage labor, business, petty business, vegetable farming and foreign labor migration (Koirala, 2006;Rai, 2009;Khatiwada, 2010;Rai, 2011). People in the high Himalayas pursue different types of livelihood activity for adaptation.…”
Section: Introductionmentioning
confidence: 99%